Frequent intergenotypic recombination between the non-structural and structural genes is a major driver of epidemiological fitness in caliciviruses. Issue 2 (16th September 2021) - Mahar, Jackie E; Jenckel, Maria; Huang, Nina; Smertina, Elena; Holmes, Edward C; Strive, Tanja; Hall, Robyn N
Abstract: The diversity of lagoviruses ( Caliciviridae ) in Australia has increased considerably in recent years. By the end of 2017, five variants from three viral genotypes were present in populations of Australian rabbits, while prior to 2014 only two variants were known. To understand the evolutionary interactions among these lagovirus variants, we monitored their geographical distribution and relative incidence over time in a continental-scale competition study. Within 3 years of the incursion of rabbit haemorrhagic disease virus 2 (RHDV2, denoted genotype GI.1bP-GI.2 [polymerase genotype]P-[capsid genotype]) into Australia, two novel recombinant lagovirus variants emerged: RHDV2-4e (genotype GI.4eP-GI.2) in New South Wales and RHDV2-4c (genotype GI.4cP-GI.2) in Victoria. Although both novel recombinants contain non-structural genes related to those from benign, rabbit-specific, enterotropic viruses, these variants were recovered from the livers of both rabbits and hares that had died acutely. This suggests that the determinants of host and tissue tropism for lagoviruses are associated with the structural genes, and that tropism is intricately connected with pathogenicity. Phylogenetic analyses demonstrated that the RHDV2-4c recombinant emerged independently on multiple occasions, with five distinct lineages observed. Both the new RHDV2-4e and -4c recombinant variants replaced the previous dominant parental RHDV2 (genotype GI.1bP-GI.2) in their respective geographical areas, despite sharing an identical or near-identical (i.e. single amino acid change) VP60 major capsid protein with the parental virus. This suggests that the observed replacement by these recombinants was not driven by antigenic variation in VP60, implicating the non-structural genes as key drivers of epidemiological fitness. Molecular clock estimates place the RHDV2-4e recombination event in early to mid-2015, while the five RHDV2-4c recombination events occurred from late 2015 through to early 2017. The emergence of at least six viable recombinant variants within a 2-year period highlights the high frequency of these events, detectable only through intensive surveillance, and demonstrates the importance of recombination in lagovirus evolution.